Classification System in Adolescent Idiopathic Scoliosis, - Kılıç, B., Zekioğlu, A., Çatıkkaş, F., Yücel, A. S., (My University, 2014)
Scoliosis is defined as the lateral spinal curvature with a 10° Cobb angle or above. Idiopathic scoliosis accounts for nearly 80% of the structural coronal deformities. According to the age groups, it is classified as infantile (the ages between 0-3), juvenile (ages between 4-9), adolescence (the age of 10 – until maturity). King classification and Lenke classification are the mostly widely used classifications in idiopathic scoliosis classification systems. Although the classification system presented by Peking Union Medical College (PUMC) is simple and easy to understand, Lenke system is considered more advantageous for practical use. Lenke classification is the most widely used and accepted classification system.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Classification; Idiopathic Scoliosis; Spine Deformity